2021
DOI: 10.1177/21582440211032675
|View full text |Cite
|
Sign up to set email alerts
|

Television News Coverage of COVID-19 Pandemic in Nigeria: Missed Opportunities to Promote Health Due to Ownership and Politics

Abstract: This study examined Television news coverage of COVID-19 pandemic in Nigeria from February 2020 to July 2020. The focus was on African Independent Television (AIT), a privately owned TV, and Nigerian Television Authority (NTA), a government-owned TV. We also interviewed ( n = 30) participants to understand their view on media coverage of the pandemic. We found that the TV stations paid adequate attention to the issues of COVID-19. However, the private media allocated more prominence to the coverage of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…We speculate that this might be due to the content broadcasted via traditional media during the COVID-19 outbreak. A content analysis study of COVID-19 reports revealed that traditional media coverage concentrated on macrolevel information of the pandemic’s development, such as updating the relevant statistics of infections and deaths [ 65 ], which would increase individuals’ perceived severity of COVID-19. However, people may find it difficult to relate macrolevel information to personal life, resulting in this media channel having no significant impacts on personally relevant factors such as perceived susceptibility, benefits, barriers and cues to action.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this might be due to the content broadcasted via traditional media during the COVID-19 outbreak. A content analysis study of COVID-19 reports revealed that traditional media coverage concentrated on macrolevel information of the pandemic’s development, such as updating the relevant statistics of infections and deaths [ 65 ], which would increase individuals’ perceived severity of COVID-19. However, people may find it difficult to relate macrolevel information to personal life, resulting in this media channel having no significant impacts on personally relevant factors such as perceived susceptibility, benefits, barriers and cues to action.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a research by Apuke and Omar (2021) on how television covered COVID-19 in Nigeria discovered that the Nigerian television stations paid adequate attention to issues of the pandemic. The study however showed that private television stations allocated more time to the coverage of COVID-19 than public television stations.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…This really indicates that the mass media have a crucial role to play during pandemic. Other scholars who carried out studies on the role of mass media in preventing the spread of the coronavirus pandemic also affirm that the mass media provide adequate coverage of the pandemic, irrespective of some shortcomings, thereby reducing the extent to which the disease would have caused havoc to human health and the society [50,51,7,52,[53][54][55]33]. According to Arinze-Umobi & Chiweta-Oduah [51]:…”
Section: Mass Media Responsibility During Coronavirus In Nigeriamentioning
confidence: 99%